Jesuit accounts of the colonial Americas : intercultural transfers, intellectual disputes, and textualities - Donato, Clorinda; Lüsebrink, Hans-Jürgen; Bernier, Marc André, 1964- (UCLA Clark Memorial Library series., 2014)
Linking Jesuit texts, the rhetorical tradition, and the newly emerging anthropology of the Enlightenment, this collection traverses the vast expanses of Old and New World France and Spain in fascinating new ways.